2018
DOI: 10.18203/2349-2902.isj20181113
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tumor size and immunohistochemistry status with lung metastasis in carcinoma breast

Abstract: Background: Breast cancer is common cancer among females in rural India and is rapidly catching up to cervical cancer in rural India. Metastasis can occur after the initiation of treatment or at the time of diagnosis. The stage at initial presentation and underlying biology of the tumor has an impact on prognosis and metastasis of the tumor. The objective of the study was to study the correlation between tumor size and lung metastasis and to find the correlation between ER, PR status, and lung metastasis.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…However, breast cancer prevalence was higher in the age group above 40 years (79.26%) compared to those under 40 years old. 8 That finding is in accordance with our study where it was found that in the metastasis occurred more often in patients aged 45 years (71.9%) than patients aged < 45 years (28.1%).…”
Section: Resultssupporting
confidence: 93%
“…However, breast cancer prevalence was higher in the age group above 40 years (79.26%) compared to those under 40 years old. 8 That finding is in accordance with our study where it was found that in the metastasis occurred more often in patients aged 45 years (71.9%) than patients aged < 45 years (28.1%).…”
Section: Resultssupporting
confidence: 93%